Thresholds of Toxicological Concern for cosmetics-related substances: New database, thresholds, and enrichment of chemical space. (November 2017) - Yang, Chihae; Barlow, Susan M.; Muldoon Jacobs, Kristi L.; Vitcheva, Vessela; Boobis, Alan R.; Felter, Susan P.; Arvidson, Kirk B.; Keller, Detlef; Cronin, Mark T.D.; Enoch, Steven; Worth, Andrew; Hollnagel, Heli M.
Abstract: A new dataset of cosmetics-related chemicals for the Threshold of Toxicological Concern (TTC) approach has been compiled, comprising 552 chemicals with 219, 40, and 293 chemicals in Cramer Classes I, II, and III, respectively. Data were integrated and curated to create a database of No-/Lowest-Observed-Adverse-Effect Level (NOAEL/LOAEL) values, from which the final COSMOS TTC dataset was developed. Criteria for study inclusion and NOAEL decisions were defined, and rigorous quality control was performed for study details and assignment of Cramer classes. From the final COSMOS TTC dataset, human exposure thresholds of 42 and 7.9 μg/kg-bw/day were derived for Cramer Classes I and III, respectively. The size of Cramer Class II was insufficient for derivation of a TTC value. The COSMOS TTC dataset was then federated with the dataset of Munro and colleagues, previously published in 1996, after updating the latter using the quality control processes for this project. This federated dataset expands the chemical space and provides more robust thresholds. The 966 substances in the federated database comprise 245, 49 and 672 chemicals in Cramer Classes I, II and III, respectively. The corresponding TTC values of 46, 6.2 and 2.3 μg/kg-bw/day are broadly similar to those of the original Munro dataset. Graphical abstract: Highlights: COSMOS TTC dataset is a new TTC dataset comprising 552 cosmetics-related chemicals. It expands the coverage of chemical space for cosmetics-related chemicals. Human thresholds of 42 for Class I and 7.9 μg/kg-bw/day for Class III are derived. No human threshold is proposed for Cramer Class II due to insufficient data. Combining COSMOS and Munro datasets gives similar thresholds to Munro TTC values.